Local restaurant business performance during pandemic covid-19: a case of Nias Island, Indonesia - Anggraeni Permatasari; Apta Lentani Zebua (International Journal of Family Business Practices, 2022)
The purpose of this study is to encourage entrepreneurs who are motivated to make deliberate decisions to follow their dreams. This study aims to determine the factors that motivate and hinder restaurant entrepreneurs from maintaining their businesses during the Covid-19 pandemic. This study used a qualitative method with a single case study approach. Data were collected through interviews and observations. This study involved five informants who owned a pork restaurant business in Nias Island, Indonesia. The data analysis was performed using the GIOIA method. The results showed that three factors motivated entrepreneurs to keep running their businesses during the pandemic: socio-economic factors, self-fulfillment and family business longevity, and customer trust and loyalty. The findings also revealed barriers related to the sustainability of pork restaurants in the local area. This study identified four main barriers during the Covid-19 pandemic such: decreasing number of customers, scarcity of raw materials, lack of knowledge in business strategy, and limitations in fund resources. This study develops a solution to sustain pork restaurants in local areas during pandemic